Agronomic responses of diverse cowpea cultivars to planting date and cropping system - Ewansiha, S.U.; Kamara, A.; Chiezey, U.F.; Onyibe, J.E. (2014)
Cowpea-maize intercropping causes low yields of cowpea due to shading effect by maize plants. Staggering of dates of planting of cowpea in an intercrop is a potential way of reducing intercrop shading while increasing cowpea yield. Nonetheless, contrasting cowpea cultivars may have differential response to planting dates. A field trial was conducted in 2008 and 2009 growing seasons at Samaru in Nigerian Guinea savannah to determine the performance of diverse cowpea cultivars intercropped with maize 4, 6 and 8 weeks after planting maize. The trial was laid out in a split-split-plot design. Grain yield and crop value were stable (1,110.5-1,163.5 kg ha-1, $2,379.3-2,566.8 ha-1, respectively) among planting dates. Sole cowpea was more productive than intercropped cowpea for number of branches (11 vs. 5 m-2), peduncles (41 vs. 24 m-2), pods (69 vs. 48 m-2) and seed (569 vs. 406 m-2), fodder yield (2685 vs. 1889 kg ha-1) and grain yield (1479 vs. 797 kg ha-1). Number of pods and seeds, seed weight and fodder yield were positive key traits of cowpea grain yield. Rankings of cowpea cultivars in terms of grain yield did not change with cropping system suggesting that cowpea cultivars that have superior yield in sole crops can be recommended for intercropping with maize. Grain yield of intercropped cowpea and crop value of maize plus cowpea and that of intercropped cowpea were highest for late maturing and indeterminate cowpea. Therefore, late and indeterminate cowpea cultivars should be preferred for intercropping with maize.